Implementation of School Zoning System Policy for Prospective New Students on the Border of Bandar Lampung City and South Lampung Regency - Apriyani, Yuyun; Yulianto, Yulianto; Meutia, Intan Fitri; Hermawan, Dedy (The Eastasouth Journal of Social Science and Humanities, 2025)
The zoning policy in New Student Admissions (PPDB) aims to equalize access and quality of education in Indonesia. This study analyzes the implementation of the zoning policy for prospective new students on the border of Bandar Lampung City and South Lampung Regency, focusing on SMP Negeri 24 Bandar Lampung and SMP Negeri 1 Tanjung Bintang. Data were obtained through interviews, observations, and document studies. The study shows that the main obstacle is administrative inconsistency even though the distance criteria have been met. Policy recommendations include increasing socialization and revising regulations to accommodate the needs of border communities.